The 20th Asia and South Pacific Design Automation Conference 2015
DOI: 10.1109/aspdac.2015.7059056
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing MLC PCM write energy for free through profiling-based state remapping

Abstract: Phase change memory is becoming one of the most promising candidates to replace DRAM as main memory in deep sub-micron regime. Multi-level cell (MLC) PCM outperforms single level cell (SLC) PCM in terms of storage capacity but requires an iterative programming-and-verifying scheme to program cells to different resistance levels. The energy consumed in programming different MLC states varies significantly, thus motivating a state remapping technique to minimize the overall write energy. In this paper, we first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The method improves system performance by 19.2%, and memory energy efficiency by 14.4% over the state-of-the-art MLC PCM baseline system, which does not employ bit decoupling. Zhao et al [2015] found that dynamic state remapping (DSR) generates locally optimal remapping decisions without considering the similarity between the new data and the old data stored in the memory. Therefore, when redundant write elimination (RWE) is applied, DSR may not be optimal, since it possibly introduces more transitions and more energy consumption.…”
Section: Mapping and Buffering Data In Mlc Pcmmentioning
confidence: 99%
“…The method improves system performance by 19.2%, and memory energy efficiency by 14.4% over the state-of-the-art MLC PCM baseline system, which does not employ bit decoupling. Zhao et al [2015] found that dynamic state remapping (DSR) generates locally optimal remapping decisions without considering the similarity between the new data and the old data stored in the memory. Therefore, when redundant write elimination (RWE) is applied, DSR may not be optimal, since it possibly introduces more transitions and more energy consumption.…”
Section: Mapping and Buffering Data In Mlc Pcmmentioning
confidence: 99%
“…(1) while not empty do (2) if there is an V with degree ≤ then (3) delete V (4) else (5) obtain the frequency set by offline profiling (6) sort variables based on the descending write cost (7) choose V with MAX COST (8) add V to spilling list (9) delete V (10) end if (11) if no variable has been spilled then (12) color the variables in reverse order of deleting (13) else (14) spill each V ∈ everywhere (15) rebuild the interference graph and repeat the procedure (16) end if (17) end while Algorithm 2: SSCM-based register allocation algorithm. Thus, all accesses take the same amount of time.…”
Section: Methodsmentioning
confidence: 99%
“…The consumed energy is accumulated by each 2-bit state transition in the register. Each register is 64-bit long and the bits in the same register can be programmed simultaneously [7]. For every register, the overall energy consumption is determined by the product of each state to program and the energy of each state.…”
Section: Dynamic Energymentioning
confidence: 99%
See 1 more Smart Citation
“…This property is utilized to respectively represent "0" and "1". Furthermore, with more fine-grained resistance partitions, each cell can represent multiple bits [8,9]. Writing to PCM requires heating the phase change material, which is more time consuming than reading.…”
Section: Pcm Preliminariesmentioning
confidence: 99%